2017
DOI: 10.1016/j.jseaes.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical record of methane seepage in authigenic carbonates and surrounding host sediments: A case study from the South China Sea

Abstract: Sediments at marine methane seep sites provide potential archives of past fluid flow that serve to explore seepage activities over time. Three gravity cores (D-8, D-F, and D-7) were collected from seep sites on the northern slope of the South China Sea where gas hydrates were drilled in the subsurface. Various carbon and sulfur contents, δ 13 C values of total inorganic carbon (δ 13 C TIC), δ 34 S values of chromium reducible sulfur (δ 34 S CRS), trace element contents, grain size, and AMS 14 C dating of plank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 86 publications
3
14
0
Order By: Relevance
“…In this model, phosphate concentration profiles were used to constrain the initial age of POC. Due to the lack of phosphate concentration profiles in the cores of Dongsha, initial ages in Dongsha (5000 yr) were adopted from Hu et al [54]. For the same reason, the initial ages of 2015XS-44 and 2015XS-50 in Xisha were assumed to be the same as that of 2015XS-R2 derived from a measured phosphate concentration profile.…”
Section: 2mentioning
confidence: 99%
“…In this model, phosphate concentration profiles were used to constrain the initial age of POC. Due to the lack of phosphate concentration profiles in the cores of Dongsha, initial ages in Dongsha (5000 yr) were adopted from Hu et al [54]. For the same reason, the initial ages of 2015XS-44 and 2015XS-50 in Xisha were assumed to be the same as that of 2015XS-R2 derived from a measured phosphate concentration profile.…”
Section: 2mentioning
confidence: 99%
“…Recent studies have demonstrated that in rapidly depositing methane‐rich marine sedimentary environments, enrichment of CRS (δ 34 S CRS ) and molybdenum (Mo) can be used as proxies to identify paleo‐SMTZs and methane seepage events in marine sediments (Chen et al, ; Hu et al, ; Li et al, ; Lin et al, ; Peketi et al, , ). Negative correlation between CRS content and χ lf in sediment cores MD161/Stn8, MD161/Stn13, and NGHP‐01‐10D (Figure e; Badesab et al, ) suggests that magnetic tracking in combination with geochemical proxies (CRS, δ 34 S CRS , Mo) can be used to constrain paleo‐SMTZ and methane seepage events in marine sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by comparing the depth profiles of CaCO 3 content in CL44 and CL47 with that in an adjacent core (SO49-37KL) with established Marine Isotope Stage, we found that the upper~2 m sediments of CL44 and CL47 represent normal hemipelagic background deposition during the Holocene (Figure S3) 8 Geofluids Figure S4). In contrast, the layers at the interval of~1.4 to~4.2 mbsf in CL44 and~1.8 to~5 mbsf in CL47 exhibiting high Si, Ti, and Zr/Rb contents and coarser grain sizes ( Figure S4) suggest elevated input of detrital fraction during sea-level lowstands [71,72]. In addition, the flat seafloor topography in the study area also precludes the occurrence of abrupt depositional event such as landslide (Figure 1).…”
Section: Formation Mechanisms Of the Nonlinear Porewatermentioning
confidence: 94%